1980
DOI: 10.1017/s0043174500061622
|View full text |Cite
|
Sign up to set email alerts
|

Growth Analysis of Soybeans (Glycine max) in Competition with Velvetleaf (Abutilon theophrasti)

Abstract: Field experiments were conducted to study the effects of varying velvetleaf (Abutilon theophrastiMedic.) densities and planting dates on the growth and yield of soybeans [Glycine max(L.) Merr. ‘Amsoy 71’]. Velvetleaf densities ranging from 2.5 to 40 plants/m2caused reductions in the dry weight of soybean leaves, stems, roots, and pods and seeds, and in the leaf area index, pod number, and seed yield when velvetleaf and soybean plants emerged at the same time. The magnitude of reduction in soybean growth and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
65
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 5 publications
9
65
1
Order By: Relevance
“…Staniforth (1965) determined that yields were depressed 31% when 3 velvetleaf/ 30 cm of row remained for the entire growing season. Hagood et al (1980) also confirmed that increasing velvetleaf densities would cause greater soybean yield losses. Full-season densities of only 2.5 velvetleaf/m^ of soil surface (randomly located weeds) caused significant yield reduc tions (26%).…”
Section: Complete Defoliation (Leaflet Picking and Across-the-midrib supporting
confidence: 52%
See 3 more Smart Citations
“…Staniforth (1965) determined that yields were depressed 31% when 3 velvetleaf/ 30 cm of row remained for the entire growing season. Hagood et al (1980) also confirmed that increasing velvetleaf densities would cause greater soybean yield losses. Full-season densities of only 2.5 velvetleaf/m^ of soil surface (randomly located weeds) caused significant yield reduc tions (26%).…”
Section: Complete Defoliation (Leaflet Picking and Across-the-midrib supporting
confidence: 52%
“…Increasing full-season morningglory densi ties to 1 weed/15 cm of row resulted in soybean LAI reductions of 60%. Hagood et al (1980) reported that soybeans competing with 10 velvetleaf/ of soil surface displayed an LAI of 3.5 to 3.9 by 11 or 12 weeks after emergence. In contrast, weed-free soybeans possessed an LAI of 6.3 to 6.6 after the same interval had passed.…”
Section: Complete Defoliation (Leaflet Picking and Across-the-midrib mentioning
confidence: 99%
See 2 more Smart Citations
“…The malvaceous weed, velvetleaf, interferes with the growth of several crops including com (Zea mays L.) (DeFelice, Witt and Slack 1984), cotton (Gossypium hirsutum L.) (Chandler, 1977) and soybeans [Glycine max (L.) Merr.] (Eaton, Russ and Feltner, 1976;Hagood et al, 1980;Dekker and Meggitt, 1983). Several investigators have attributed this interference to competition for water (Hagood et al, 1980;Dekker and Meggitt, 1983), light (Stoller and Woolley, 1985), and nutrients (Oliver, 1979), while others have implicated allelopathy (Colton and Einhellig, 1980;Bhowmick and Doll, 1982).…”
mentioning
confidence: 99%